Post-traumatic stress and major depressive disorders in parent caregivers of children with a chronic disorder. (September 2019) - Carmassi, C.; Corsi, M.; Bertelloni, C.A.; Pedrinelli, V.; Massimetti, G.; Peroni, D.G.; Bonuccelli, A.; Orsini, A.; Dell'Osso, L.
Highlights: PTSD and MDD are the main psychopathological conditions that affect pediatric caregivers. In parents of children with epilepsy we detected rates of 15.7% and 7.5% of DSM-5 PTSD and MDD, respectively. Mothers who witness generalized seizures are more likely to also experience symptoms of depression. Post-traumatic stress spectrum symptoms seem to be linked to depressive symptoms. Abstract: Post-traumatic Stress Disorder (PTSD) and Major Depressive Disorder (MDD) are the most common psychiatric consequences among caregivers of pediatric patients affected by severe chronic illnesses. The aims of this study were to describe rates of PTSD and MDD in a sample of parents of epileptic children, and to examine the correlations between symptoms of post-traumatic stress and depression. Parents of children with epilepsy were enrolled and screened by means of the PTSD module of the Semi-Structured Clinical Interview for DSM-5 (SCID-5) and of the Hamilton Rating Scale for depression (HAM-D). They also completed the Trauma and Loss Spectrum Self-Report (TALS-SR), an international instrument to evaluate post-traumatic stress spectrum symptoms. Results revealed PTSD rates of 15.7% (19.5% mothers, 8, 1% fathers; p = .043) and MDD rates of 7.5% (10.2% mothers, 1.8% fathers; p = .064). A model of multiple linear regression indicated a significant B linear regression coefficient between being mothers ( p = .012), witnessing tonic-clonic seizures ( p = .015) and having higher TALS-SR total score ( p < .001) as predictors of HAM-D total score. Our findings highlight the relationship between PTSD and MDD, evidencing the need for further studies on pediatric caregivers aimed to develop specific intervention programs of healthcare prevention and assistance.